Human Telomere Repeat Binding Factor TRF1 Replaces TRF2 Bound to Shelterin Core Hub TIN2 when TPP1 Is Absent - Janovič, Tomáš; Stojaspal, Martin; Veverka, Pavel; Horáková, Denisa; Hofr, Ctirad (Journal of molecular biology, 2019)
Human telomeric repeat binding factors TRF1 and TRF2 along with TIN2 form the core of the shelterin complex that protects chromosome ends against unwanted end-joining and DNA repair. We applied a single-molecule approach to assess TRF1-TIN2-TRF2 complex formation in solution at physiological conditions. Fluorescence cross-correlation spectroscopy was used to describe the complex assembly by analyzing how coincident fluctuations of differently labeled TRF1 and TRF2 correlate when they move together through the confocal volume of the microscope. We observed, at the single-molecule level, that TRF1 effectively substitutes TRF2 on TIN2. We assessed also the effect of another telomeric factor TPP1 that recruits telomerase to telomeres. We found that TPP1 upon binding to TIN2 induces changes that expand TIN2 binding capacity, such that TIN2 can accommodate both TRF1 and TRF2 simultaneously. We suggest a molecular model that explains why TPP1 is essential for the stable formation of TRF1-TIN2-TRF2 core complex.
Keywords: Telomeric Repeat Binding Protein 1; shelterin; Models, Molecular; Protein Multimerization; assembly; shelterinový komplex; DNA-Binding Proteins; Humans; Telomere-Binding Proteins; Telomeric Repeat Binding Protein 2; telomerasa; DNA vazebné proteiny; protein TRF1; telomery; telomere; Protein Binding; Telomerase; lidé; proteinové domény; molekulární modely; proteiny vázající telomery; Telomere; TIN2; protein TRF2; vazba proteinů; Protein Domains; Shelterin Complex; multimerizace proteinu; single-molecule